Alterations in the Urinary Microbiota Are Associated With Cesarean Delivery - Liu, Fengping; Lv, Longxian; Jiang, Huiyong; Yan, Ren; Dong, Shurong; Chen, Liping; Wang, Wei; Chen, Yong Q. (Frontiers in Microbiology, 2018)
Similar to the gut, the bladder contains urinary microbiota, and its bacterial composition and structure are determined by the individual’s health status. Cesarean section is a traumatic event for women and it is correlated with postpartum complications. To better understand the urinary microbiota alterations caused by cesarean section, 16S rDNA sequencing was used to assess urine specimens collected by transurethral catheterization from 30 healthy women undergoing cesarean section pre-delivery (PreD) and post-delivery (PostD). A significant increase in bacterial diversity and more detectable bacteria at the phylum, family, and genus levels was observed in the PostD group compared to the PreD group, indicating that cesarean delivery altered the bacterial community. Specifically, the phylum Firmicutes and its affiliated family Lactobacillaceae and genus Lactobacillus dramatically decreased in the PostD group, suggesting that beneficial bacteria decreased after cesarean section, a process that includes surgery and delivery, and clinicians should be aware that this might promote complications. Concurrently, the phylum Proteobacteria and its affiliated bacteria Pseudomonadaceae and Pseudomonas increased in the PostD group compared to the PreD group. This indicates that pathogen growth increases after cesarean section, making it important for clinicians to combat these changes to protect women from infectious diseases. In addition, functional pathway analysis revealed that several metabolic pathways, such as metabolism of energy, cofactors and vitamins, were strengthened in the PostD group, whereas membrane transport was lessened in this group. This suggests that women’s metabolic disorders might be cured by balancing urinary microbiota. Interestingly, several bacteria were correlated with back pain among postpartum women. Overall, the altered urinary microbiota between the PreD and PostD periods appears to provide insight into how to prevent postpartum complications.